PERBEDAAN TINGKAT KEPUASAN PASIEN NON JKN DENGAN JKN TERHADAP PELAYANAN POLIKLINIK GIGI DI FASKES TINGKAT I - Titin Clarita Siagian; Suci Erawati (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2020)
The public health center as one of the public service institutions that is influenced by the development of health science, technological advancements and the socio-economic life of the community must be able to improve quality services and satisfy customers. The purpose of this study was to determine differences in the level of satisfaction of non JKN and JKN patients with dental polyclinic services at Health Center I Health Center Amplas City Medan. This research method is inductive comparative with cross sectional approach. The population is to use the average registered patient visits registered at 15,249 patients, the way of taking samples with proportional sampling of 100 respondents. The statistical test uses the Mann-Whitney U Test with the help of a statistical program on the computer. The results showed that there were differences in the level of satisfaction of non JKN patients with the level of JKN patient satisfaction in Amplas City Health Center Medan (p value = 0,000).